EVALUASI WEBSITE SMK NEGERI KOTA PALEMBANG MENGGUNAKAN USABILITY TESTING - Febriyanti Panjaitan; Siti Sauda (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
Website is a technological facility that can help introduce or promote an agency, institution or school. To see the level of ease of use of the website on SMKN Palembang measurement of the web site services. Measuring level of user convenience using the method of Usability Testing. Usability testing is an attribute to assess how easy to use website interface, which has five components, namely Learnability, Efficiency, Memorability, Error, and Satisfaction. Website at each school for the users of the website by using the method of Usability Testing concluded that the average website has points are good enough and can be used by users, especially in the variable learnability the average school scored > 60%, where in the category table measurement of usability presentation in the category enough. Each school each user has different responses in the delivery of questionnaires with questions based on the categories of Usability Testing methods.